2009
DOI: 10.1128/jvi.00280-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Percentage of Human Immunodeficiency Virus Type 1 Sequences That Are Hypermutated and Markers of Disease Progression in a Longitudinal Cohort, Including One Individual with a Partially Defective Vif

Abstract: Hypermutation, the introduction of excessive G-to-A substitutions by host proteins in the APOBEC family, can impair replication of the human immunodeficiency virus (HIV). Because hypermutation represents a potential antiviral strategy, it is important to determine whether greater hypermutation is associated with slower disease progression in natural infection. We examined the level of HIV-1 hypermutation among 28 antiretroviral-naive Kenyan women at two times during infection. By examining single-copy gag sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…Proviruses with footprints of past cytidine deamination are found in many infected patients independently of the HIV-1 subtype (1,15,17,33), suggesting that variation in the spectra of the anti-APOBEC3 activities of HIV-1 Vif and/or antiretroviral activity of Vif-resistant APOBEC3 proteins is important in vivo. HIV-1-infected patients with certain A3H haplotypes displayed fewer G-to-A mutations and lower viral loads (9), and it is attractive to speculate that Vif variants that counteract multiple APOBEC3 proteins decrease the complexity of the viral quasi-species as well as the pathogenicity of HIV-1 in a given infected individual.…”
Section: Discussionmentioning
confidence: 99%
“…Proviruses with footprints of past cytidine deamination are found in many infected patients independently of the HIV-1 subtype (1,15,17,33), suggesting that variation in the spectra of the anti-APOBEC3 activities of HIV-1 Vif and/or antiretroviral activity of Vif-resistant APOBEC3 proteins is important in vivo. HIV-1-infected patients with certain A3H haplotypes displayed fewer G-to-A mutations and lower viral loads (9), and it is attractive to speculate that Vif variants that counteract multiple APOBEC3 proteins decrease the complexity of the viral quasi-species as well as the pathogenicity of HIV-1 in a given infected individual.…”
Section: Discussionmentioning
confidence: 99%
“…HIVA Q23 /SIV vif , a full-length replicationcompetent clone expressing vif from SIV mac239 , was created from Q23⌬vif (46). Q23⌬vif was derived from the Q23-17 full-length molecular clone (48) and was engineered with unique SalI and MluI restriction sites at the 5Ј and 3Ј ends of vif, causing a frameshift in the endogenous vif gene and allowing for the insertion and expression of different vif variants (53).…”
Section: Methodsmentioning
confidence: 99%
“…However, even in the presence of Vif, there is evidence of A3 deaminations inducing hypermutation of integrated proviral genomes (16)(17)(18)(19)(20)(21)(22)(23). There are two ways in which this occurs.…”
mentioning
confidence: 99%
“…More detailed analysis of the signatures revealed that A3G is most active at a 5=CCC motif, and A3D can be differentiated from A3F and A3H by examining a larger surrounding sequence 3= of the cytosine (30). Studies that sequenced integrated proviral genomes have shown that proviral DNAs contain mutations in multiple sequence contexts, suggesting that multiple A3s can mutate the same genome (16)(17)(18)(19)(20)(21)(22)(23). However, what was unable to be concluded from these studies was if the mutations induced from multiple A3s occurred in a single round of replication or multiple rounds of replication.…”
mentioning
confidence: 99%